PENGARUH PENGGUNAAN APLIKASI E-COMMERCE, DALAM SALAH SATU MEDIA SOSIAL INSTAGRAM UNTUK MENINGKATKAN PENJUALAN DI PERUSAHAAN HIJUP.COM - a Gibralazhafran Iskandar, Rayhansya; Yoestini, Yoestini (Faculty of Economics and Business Diponegoro University, 2021)
Abstract This study aims to find out whether the level of influence of using the E-Commerce Instagram application on the sales of HIJUP.COM products is insignificant or significant. This research was conducted with a quantitative research method which is a study that describes or explains a problem whose results can be generalized (Kriyantono: 2010, p. 55). According to the level of interpretation, this research is an explanatory study, meaning that this study aims to examine the research variables. The reason researchers use the explanative method is to try to explain why something can happen and what the effect is. The results show that Instagram has a positive influence on HIJUP sales, even with a small number of presentations (15.5%). Although the number of HIJUP followers is high, and the use of the Instagram application in Indonesia is also high. This is a paradox because at first we could see how large the use of social media in Indonesia, and the high popularity of HIJUP companies in the Instagram application, did not have a high influence on HIJUP sales. As Marcel Prouts put it, that: